Income and Expenditure Inequalities among Households in Poland - Ostasiewicz, Katarzyna (Central and Eastern European Economic Review, 2019)
Stratification and its inverse concept, overlapping, are strictly connected with inequality, playing an essential role in one kind of decomposition of the Gini index. Properties of overlapping indexes are investigated in this paper. Decomposition of inequalities in Poland (of incomes, expenditures, and their difference), which includes the overlapping-due term, is performed and analysed.